A hybrid algorithm for one-dimensional cutting stock problem with multiple stock sizes - Phương, Phan Thị Hoài; Mai, Lương Chi; Hùng, Nguyễn Văn (Journal of Computer Science and Cybernetics, 2012)
See full text.